Community Health Financing-The Way Forward In Agogo Sub District - Takyi, B.F. (University of Ghana, 2002)
The cost of providing basic health care in Ghana is escalating and it is beyond the ability of the government alone to finance health care. The introduction of the cash and carry system although had advantages, however for the majority of the people in the rural areas the system has not been of much help as money was not always available to pay for the cost of health care. Therefore, there has been the need to find alternative method of financing health care in Ghana. Mutual health insurance has been suggested as one form of financing health care. The DHMT intends to start a Mutual Health Insurance Scheme in Agogo sub-district. Since health insurance is a new thing to the area, this exploratory study was designed to examine the knowledge and attitude of the people on community health financing. Data was collected using qualitative methods of in-depth interviews and FGDs. In all 83 participants took part in the study. Six FGDs, six key informant interviews and six in-depth interviews were conducted. The key result of the study indicates that the knowledge of health insurance was very low. People are willing to join the scheme but they should be educated about the scheme and the premium should be affordable. The premium should be collected in cash and each individual should pay a fixed rate. Divergent views expressed about the scope of services as the community wanted all service covered under the scheme while the key informants wanted out-patient services or admissions covered under the scheme only. They wanted exemption policy to be maintained and then government to give seed money to start the scheme. The study concluded that community health insurance is feasible in Agogo Sub district; The following recommendations were made following the study - Both the cash and carry system and Health Insurance should be operated side by side. - Intensive education on the concept of Health Insurance should be carried out in the Sub-district. - The scheme should start with OPD Services - Ananekrom and Bebome health centres should be up graded and - The Government should continue with the exemption policy and give seed money for the start of the scheme.